Prevalence and risk factors of helicobacter pylori in Turkey: a nationally-representative, cross-sectional, screening with the C-13-Urea breath test - ÖZAYDIN, AYŞE NİLÜFER (BMC, 2013)
Background: Helicobacter pylori is an important global pathogen infecting approximately 50% of the world's population. This study was undertaken in order to estimate the prevalence rate of Helicobacter pylori infections among adults living in Turkey and to investigate the associated risk factors. Method: This study was a nationally representative cross sectional survey, using weighted multistage stratified cluster sampling. All individuals aged >= 18 years in the selected households were invited to participate in the survey. Ninety two percent (n = 2382) of the households in 55 cities participated; 4622 individuals from these households were tested with the C-13-Urea breath test. Helicobacter pylori prevalence and associated factors were analysed by the t test, chi square and multiple logistic regression with SPSS11.0. Results: The weighted overall prevalence was 82.5% (95% CI: 81.0-84.2) and was higher in men. It was lowest in the South which has the major fruit growing areas of the country. The factors included in the final model were sex, age, education, marital status, type of insurance (social security), residential region, alcohol use, smoking, drinking water source. While education was the only significant factor for women, residential region, housing tenure, smoking and alcohol use were significant for men in models by sex. Conclusion: In Turkey, Helicobacter pylori prevalence was found to be very high. Individuals who were women, elderly adults, single, had a high educational level, were living in the fruit growing region, had social security from Emekli Sandigi, were drinking bottled water, non smokers and regular alcohol consumers, were under less risk of Helicobacter pylori infection than others.
Keywords: Helicobacter pylori prevalence; Risk factors of helicobacter pylori infection; Smoking; Alcohol use; SOCIOECONOMIC-STATUS; ASYMPTOMATIC SUBJECTS; ALCOHOL-CONSUMPTION; GASTRIC-CANCER; WATER SOURCE; INFECTION; POPULATION; EPIDEMIOLOGY; CHILDREN; ADULTS